Ellagic acid for oral mucositis: investigation of the therapeutic effect in rats - Ezgi Eroğlu Çakmakoğlu; Adalet Çelebi; Muhammet Bahaeddin Dörtbudak; Hayati Yüksel; Aydın Keskinruzgar (Biotechnology & Biotechnological Equipment)
The aim of this study was to evaluate the effect of ellagic acid on 5-fluorouracil-induced oral mucositis in rats. Twenty-four 6-month-old male Wistar albino rats were used. The rats were divided into three groups: Experimental Group I, Experimental Group II and Control Group. A superficial scratch was made on the mucosa of the right cheek pouch on the 3rd day and the 5th day. Oral mucositis protocol was applied to the Control Group. Ellagic acid was administered by gavage to the Experimental Group I from the 1st day to the 5th day along with the 5-FU procedure, and to the Experimental Group II from the 5th day to the 10th day. On the 11th day, all rats were sacrificed. The effect of ellagic acid on the healing of oral mucositis was evaluated histopathologically and immunohistochemically. TNF-α expression was observed at various intensities in the infected incision sites of the Experimental Group I sample, especially in the interstitial area in the lamina propria and mostly in the cytoplasm of the inflammatory cells within the vessel. Similar to the Experimental Group I, TNF-α expression of varying intensity occurred in the inflammatory cells in the Experimental Group II, partly in the epithelium and mostly in the inflammatory cells in the lamina propria. Additional research is needed to elucidate the pathogenic inflammatory mechanisms involved in the mucositis site and the prophylactic and therapeutic roles of antioxidants in the healing of oral mucositis by ellagic acid.